Hemp Fibres: Essentials, Composites or Nanocomposites and Technical Applications - Kausar, Ayesha; Ahmad, Ishaq (Nano-Horizons: Journal of Nanosciences and Nanotechnologies, 2023)
In this article, we overview a very important type of natural fibre, namely, hemp fibre. We consider the exclusive structure, properties, modification, the composite or nanocomposite formation and exceptional application zones. Industrial hemp fibres have been commonly developed and possess high cellulose amounts. The long hemp fibres can be termed bast or flax fibres. Hemp fibres are eco-friendly, and have light weightiness and stiffness properties. Consequently, to enhance the use of hemp fibres at engineering level, research has focused on improving the mechanical or thermal and high-tech features of these fibres. In doing this, the surface modification or treatment of hemp fibres has been notably considered. The modified fibres have been found valuable for developing certain derived materials such as polymeric composites and nanocomposites in particular. Consequently, including hemp fibres as additives in composite or nanocomposite matrices has been explored for manufacturing high performance ecological, recyclable, biodegradable and sustainable materials. Application areas identified for the hemp and related composites or nanocomposites include the synchrotron and neutron scattering, water treatment aiming dye removal, automobiles, textiles and construction. However, there is insufficient literature on these technologically important fibres and ensuing materials. Comprehensive future efforts may better resolve the challenges regarding reproducibility and long life-cycle high-tech applications of hemp fibres.